PENGARUH SEASONAL EFFECT TERHADAP RETURN SAHAM LQ-45 DI BURSA EFEK INDONESIA TAHUN 2019 – 2020 - Budiman Budiman; Nur aida Arifah Tara; I Nyoman Nugraha AP (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
The purpose of this research was to examine the existence of Monday Effect, Week Four Effect, and Rogalsky Effect on stock return of LQ-45 index ini Indonesian Stock Exchange (IDX) during 2019 – 2020. The statistic methods used to test the hypotheses are Mann Whitney. The results show that Monday Effect, Week Four Effect, and Rogalsky Effect exist on stock return of LQ-45 index in IDX.Keywords :Monday Effect, Week Four Effect, Rogalsky Effect, Return